Downregulation of Renal Hsa-miR-127-3p Contributes to the Overactivation of Type I Interferon Signaling Pathway in the Kidney of Lupus Nephritis - Wu, Lingling; Han, Xiao; Jiang, Xiaoyue; Ding, Huihua; Qi, Chaojun; Yin, Zhihua; Xiao, Jianwei; Xiong, Le; Guo, Qiang; Ye, Zhizhong; Qu, Bo; Shen, Nan (Frontiers in Immunology, 2021)
MicroRNAs are involved in the pathogenesis of systemic lupus erythematosus (SLE) and dysregulated in the kidneys of lupus nephritis (LN) patients, but their pathogenic roles in LN are largely unknown. Janus Kinase 1 (JAK1) mediates the activation of the downstream signaling pathways of many inflammatory cytokines, including type I interferon (IFN-I) signaling pathway which is critical to the development of SLE and LN. Thus, JAK1 is a potent therapeutic target for these autoimmune diseases. However, there are few studies demonstrating the dysregulation of JAK1 in autoimmune diseases and the molecular mechanism behind it. In this concise report, we show an inhibitory effect of hsa-miR-127-3p, a microRNA that is downregulated in the renal tissues of LN patients, on IFN-I signaling. We found the overexpression of hsa-miR-127-3p could inhibit the induction of ISRE and GAS mediated gene expression, the phosphorylation of STAT1 and STAT2, and the upregulation of IFN stimulated genes (ISGs) stimulated by IFN-I. While, hsa-miR-127-3p antagonist enhanced the activation of IFN-I signaling in primary renal mesangial cells. Subsequently, we identified JAK1 as a bona fide target gene of hsa-miR-127-3p and showed hsa-miR-127-3p targeted JAK1 through binding to its 3’UTR and coding region. Consistently, we found the downregulation of hsa-miR-127-3p was associated with the upregulation of JAK1 and ISGs in kidney tissues of LN patients. Our data indicate renal downregulation of hsa-miR-127-3p contributes to the overactivation of IFN-I signaling pathway in the kidneys of LN patients through promoting the expression of JAK1, suggesting hsa-miR-127-3p mimics may be used to inhibit JAK1 and IFN-I signaling pathway in LN.